Blood donation amongst people who inject drugs in Australia: research supporting policy change. Issue 3 (5th February 2020) - Quinn, Brendan; Pearson, Ruth; Cutts, Julia; Seed, Clive; Scott, Nick; Hoad, Veronica; Dietze, Paul; Wilson, David; Maher, Lisa; Thompson, Alexander; Farrell, Michael; Harrod, Mary; et al.
Abstract : Background and objectives: Until recently, people in Australia with a history of injection drug use (IDU) were deferred indefinitely from donating blood. Knowledge gaps regarding policy non‐compliance and the prevalence of blood donation practices amongst people who inject drugs (PWID) precluded changes to this policy. We sought to address these gaps and to estimate the additional risk to Australia's blood supply associated with changing the indefinite deferral policy to 1 or 5 years since last injecting episode. Materials and methods: Data on blood donation amongst PWID were collected from 1853 interviews across two Australian studies of PWID conducted during 2015/16. Mathematical modelling was used to estimate the additional risk of hepatitis C (HCV)‐infected window period collections as a result of changing the deferral policy. Results: A very few (2–4%) study participants reported ever donating blood after ≥1 IDU episode. Changing the deferral policy from indefinite to 1 or 5 years was estimated to result in an additional 0·00000070 (95%CI: 0·00000033–0·00000165) or 0·00000020 (95%CI: 0·00000008–0·00000041) HCV‐positive window period collections per year, respectively. Conclusion: Changing Australia's indefinite deferral period to 1 or 5 years since last injecting episode poses a negligible increase in the risk of HCV‐infected window period collections from blood donors with a history of IDU. Our results informed a successful submission to the Australian regulator to change the deferral period from indefinite to 5 years since last injecting episode, a policy which came into effect in September 2018.